2019
DOI: 10.1002/cam4.1894
|View full text |Cite
|
Sign up to set email alerts
|

Combined prognostic value of the cancer stem cell markers CD47 and CD133 in esophageal squamous cell carcinoma

Abstract: Background Treatments based on the inhibition of pivotal signals of cancer stem cells (CSCs) are on a promising track. Recent studies have shown that targeting CSCs with broader immune‐based therapeutic methods, for example, the anti‐CD47 treatment, may serve as a more potent strategy for eliminating these intractable cells. We aimed to explore the prognostic effects of CD47/CD133 and the potential therapeutic significance of CD47 in esophageal squamous cell carcinoma (ESCC). Methods Immunohistochemistry was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
1
19
3
2
Order By: Relevance
“…In the PFS curves of mRNAsi/corrected mRNAsi, we observed a tendency without statistical signi cance that within approximately 4 years, the PFS rate of high mRNAsi/corrected mRNAsi group was higher than that of low mRNAsi/corrected mRNAsi group. This was very different from our understanding that greater stemness of cancer cells would eventually lead to a shorter PFS [11,12]. The results might be explained by three possible causes.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In the PFS curves of mRNAsi/corrected mRNAsi, we observed a tendency without statistical signi cance that within approximately 4 years, the PFS rate of high mRNAsi/corrected mRNAsi group was higher than that of low mRNAsi/corrected mRNAsi group. This was very different from our understanding that greater stemness of cancer cells would eventually lead to a shorter PFS [11,12]. The results might be explained by three possible causes.…”
Section: Discussioncontrasting
confidence: 75%
“…Similar results were observed in the analysis of corrected mRNAsi. This nding was very different from our understanding that greater stemness of tumor cells would indicate decreased progression-free survival [11,12]. The above results indicated that the mRNAsi score in SOC samples had a close correlation with the histopathological grades.…”
Section: Resultscontrasting
confidence: 58%
“…One explanation might be that MTCs lose expression of some molecules during differentiation. The knockdown of CD47 suppressed certain stem-like properties of cancer cells, such as self-renewal and chemoresistance, suggesting that targeting CD47 could not only activate the phagocytosis of macrophages but also could be used to enhance treatment against CSCs [29]. Hence, CD47 expression may be another mechanism used by lung cancer cells, especially lung CSCs, to escape phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan J membagi usia menjadi <50 tahun dan >50 tahun dengan nilai p=0,34 namun penelitian dilakukan pada kasus kanker payudara dengan triple negative. 29,31,32 Data pada penelitian ini tidak sejalan dengan Aktas S dkk dan Baccelli I dkk. Aktas S dkk mendapatkan bahwa ekspresi CD47 meningkat seiring usia dengan nilai p yang signifikan (p=0,018), hasil yang berbeda dikarenakan menggunakan uji Chi square dan Mann whitney selain jumlah pasien lebih banyak, serta dilakukan pada kasus neuroblastoma.…”
Section: Metode Penelitianunclassified